Spatiotemporal interaction of tef head smudge disease (Curvularia spp.) and tef (Eragrostis tef) in the Western Amhara Region, Ethiopia, under the moderate (SSP245) and extreme (SSP285) climate change scenarios - Melkamu Birhanie Mekonnen; Girmaye Dires Abeje; Mequannent Andualem Mekonnen (PLoS ONE, 2026)
Tef is an important food security orphan crop in the Western Amhara Region, Ethiopia. However, its production is constrained by tef head smudge disease caused by Curvularia spp . Therefore, this study aims to model the spatiotemporal dynamics of tef head smudge disease and tef, as well as their spatiotemporal interaction. Therefore, this study conducted a comprehensive analysis of the current and projected geographic distribution of tef head smudge disease and tef by 2050 and 2070 under SSP245and SSP285 climate change scenarios using the MaxEnt model. The model has achieved 89.3% – 90.5% accuracy for tef and over 93% accuracy for tef head smudge disease across the current and future climate change scenarios. Tef is predicted to cover 33% of the Western Amhara region under the current climate scenario. However, its projections indicate shifts to 23.1% under SSP245 and 40.6% under SSP285 by 2050. By 2070, tef is projected to cover around 33.7% and 19.97% of the region under SSP245 and SSP285, respectively. Tef head smudge disease is predicted to occur on about 10,951 ha of land under the current climate change scenario. However, its distribution is predicted to be 6,361 ha and 18,812 ha by 2050 under SSP245 and 285, respectively. However, tef head smudge disease and tef are predicted to overlap on 9,659 ha of land under the current climate change scenario. This overlap is expected to increase to around 15,846 hectares (SSP285) by 2050, but decrease to 3,334 hectares (SSP285) by 2070. This study highlights the compounded challenges of climate change and disease pressure on tef production. Therefore, this research provides critical insights for policymakers and researchers to enhance resilience in tef cultivation and safeguard food security in the face of climate change.